Effect of DCRP and DCSP Polarity on SMAW Welding on the Depth of Penetration with E7018 Electrodes using Low Carbon Steel ASTM A36 - Ma'mun Hidayat; Helleni Febnesia; Sulaeman Deni Ramdani (Universitas Negeri Malang, 2021)
The study aims to determine the level of penetration depth using SMAW (Shielded Metal Arc Welding) Process based on the polarity type of DCRP (Direct Current Reverse Polarity) and DCSP (Direct Current Straight Polarity). This research used ASTM A36 low carbon steel plate with thickness of 6 mm and length of 200 mm, Electrode E7018 LB-52-18 ∅ 3.2 mm, and with current parameters of 90 A, 100 A, 110 A, 120 A and 130 A and 70° welding arc angle. The method used the experimental research. Data collection techniques applied direct observation techniques and descriptive statistical data analysis techniques. Testing the penetration depth of the welds with a macrographic test was conducted by an optical microscope. The test results show that DCRP has more depth than DCSP when the current is 90 A with a difference of 0.38 mm. When the current is 100 A, DCRP is deeper with a difference of 0.312 mm compared to DCSP. The third experiment, with a current of 110 A DCRP, was deeper with a difference of 0.05 mm compared to DCSP. During the fourth and fifth experiments, DCRP was deeper with a difference of 0.21 mm compared to DCSP at 120 A and DCRP was 0.324 mm deeper than DCSP at 130 A. It can be concluded that the effect of DCRP and DCSP polarity on the depth of penetration using E7018 electrodes and ASTM low carbon steel A36, DCRP polarity has a deeper penetration depth compared to DCSP.